An assessment of air pollution level using air quality index in Udaipur city, Rajasthan - Purnima Singh (National Geographical Journal of India, 2024)
Udaipur, a prominent tourist destination with a population of 451,000 according to the 2011 census, is designated as a non-attainment city under the National Clean Air Program due to its failure to meet air quality standards. The city is actively implementing an action plan to reduce air pollution, and this paper, based on secondary data, explores the achievements and challenges faced in this endeavor. Key strategies include integrated efforts in planning and managing public transport, waste disposal, domestic cooking, reducing road and construction dust, controlling industrial emissions, and raising public awareness. The paper highlights that pollution levels in Udaipur are highest during the winter season, lower in the summer, and lowest during the rainy season.